STEM, serious games, and parental involvement in special education: a systematic review - Chaidi, Irene; Kefalis, Chrysovalantis; Bakola, Lizeta N.; Drigas, Athanasios; Karagiannidis, Charalampos (Frontiers in Computer Science, 2025)
Emerging technologies, assistive technology, and STEM approaches have emerged as important knowledge-acquisition instruments in contemporary educational practices. These resources support individualized education for those with disabilities, such as autism spectrum disorder (ASD), as well as those who are typically developing. Since parents can provide vital information about a child’s temperament, learning preferences, and developmental needs, parental participation has been acknowledged as a significant determinant in children’s educational success. With educational goals in mind, serious games (SGs) provide dynamic and captivating learning environments that improve skill development. The role of parental participation in STEM education and in co-creating serious games for people with ASD is methodically investigated in this scoping review. Twenty of the 334 studies that were reviewed in accordance with PRISMA guidelines met the inclusion criteria. The findings show that active parental involvement empowers parents and children, encourages individualized learning, and increases the efficacy of educational initiatives. A promising strategy for enhancing learning, socializing, and quality of life for people with ASD is the integration of STEM, serious gaming, and parental involvement.